Versions of Switched Reluctance Generatior Design at a Constant Stator Configuration - Nikolay Grebennikov; Alexander Kireev (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The investigation of the influence of the number of phases of switched reluctance generator (SRG) to the pulse of electromagnetic torque was carried out. The computer model was created. The amplitude of torque ripples reduces to 6 times with increasing of the ripple frequency to 5 times, that is more acceptable in terms of requirements.